Prevalence, characteristics, and plasmid dynamics of mcr-1 positive Enterobacteriaceae in Hainan, China: a preliminary genomic investigation - Wang, Suimei; Han, Xiaosheng; Sheng, Yan; Zhou, Wang; Huang, Hui; Wei, Xiaobin (Frontiers in Microbiology, 2026)
IntroductionThe global spread of the plasmid-mediated colistin resistance gene mcr-1 poses a serious threat to public health. This study aimed to conduct a preliminary characterization of the epidemiology and genomic features of Enterobacteriaceae carrying the mcr-1 gene in a hospital setting in Hainan, China.MethodsA total of 2,700 Enterobacteriaceae strains, including 2,200 fecal samples and 500 respiratory, blood, and urine isolates, were collected from Haikou People’s Hospital between October 2020 to September 2024. Specifically, the mcr-1 gene was screened by PCR. Antimicrobial susceptibility testing was performed with the VITEK 2 system. Four mcr-1 positive strains underwent whole-genome sequencing using Illumina and Nanopore platforms, which were combined with CARD, multilocus sequence typing (MLST), and plasmid analysis to elucidate resistance mechanisms.ResultsThe positivity rate for mcr-1 was 0.15% (4/2,700). All positive isolates were identified as Escherichia coli, with two strains originating from urine and two from fecal samples. Antimicrobial susceptibility testing showed that the urine isolates (C29 and C180) were extensively drug resistant (XDR). The fecal strain S321.4 was multidrug resistant (MDR), while S118.1 was sensitive. Patients with XDR/MDR strains had recent antibiotic exposure and invasive procedures. Whole-genome analysis revealed that MLST types of the strains were diverse (ST410, ST167, ST11165, ST1266), and mcr-1 was located on plasmids of IncI2 or IncX4 types. The IncI2 plasmid carried a complete conjugative operon. Plasmid C180_5 harbored blaCTX-M-199 through IS150, forming a multidrug resistance plasmid. Strain C29 exhibited a reduced colistin minimum inhibitory concentration (MIC) of 0.5 μg/mL due to disruption of mcr-1 by IS3, which likely impairs gene function. However, this requires further functional validation.ConclusionThis preliminary study indicates a low prevalence of mcr-1 in our setting. However, the genomic identification of conjugative plasmids, including one carrying both mcr-1 and an extended-spectrum β-lactamase gene, highlights a tangible risk for horizontal co-transfer of resistance. The association of these isolates with healthcare exposures underscores the need for ongoing surveillance to monitor plasmid evolution in hospital ecosystems.